2007
DOI: 10.1183/09031936.00046107
|View full text |Cite
|
Sign up to set email alerts
|

Solitary pulmonary nodule evaluation with99mTc-methoxy isobutyl isonitrile in a tuberculosis-endemic area

Abstract: High prevalence of tuberculosis increases the odds for nonmalignant solitary pulmonary nodules (SPNs). Positron emission tomography (PET) using 18 F-fluorodeoxyglucose is the method of choice for the identification of malignant SPNs requiring curative surgery. However, PET is not widely available. Technetium-99m methoxy isobutyl isonitrile (MIBI) is inexpensive, widely available and shows increased uptake in malignant SPNs. The aim of the present study was to prospectively evaluate the diagnostic value of MIBI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Other tracers such as 99m Tc-MIBI and 18 F-FDG PET also share the same limitation in the positive predictive value, and this limitation should always be borne in mind especially in the tuberculosis-endemic areas of the world [34,35].…”
Section: Discussionmentioning
confidence: 96%
“…Other tracers such as 99m Tc-MIBI and 18 F-FDG PET also share the same limitation in the positive predictive value, and this limitation should always be borne in mind especially in the tuberculosis-endemic areas of the world [34,35].…”
Section: Discussionmentioning
confidence: 96%
“…[12] Only three studies have evaluated nuclear scanning to assess pulmonary mass lesions in SA. [6,13,14] Schuurmans et al [13] found a sensitivity of 92.3% and a specificity of 91.7% for the use of technetium 99m-methoxy isobutyl isonitrile as a marker for tumour uptake. Sathekge et al [6] performed a prospective study of 30 patients to assess the accuracy of dual time point PET-CT in the assessment of SPNs in Pretoria, SA.…”
Section: Discussionmentioning
confidence: 99%
“…However, more than 95 % of SPL detected by low-dose CT screening show false positive findings due to a non-malignant final diagnosis [ 1 ]. In a tuberculosis (TB) endemic area, the prevalence of benign SPL may be even higher [ 2 ], and therefore efforts have been undertaken to establish diagnostic modalities to distinguish between malignant and benign lesions without excess perioperative mortality [ 3 ]. According to guidelines for the diagnosis of SPL, there are three possibilities to manage these patients depending on the probability of an underlying malignancy: serial CT scans, tissue biopsy, or direct surgical resection [ 4 ].…”
Section: Introductionmentioning
confidence: 99%